Powerline-Kommunikation für Batteriemanagement-Systeme in Elektro- und Hybridfahrzeugen - Opalko, Oliver (Forschungsberichte aus der Industriellen Informationstechnik / Institut für Industrielle Informationstechnik (IIIT), Karlsruher Institut für Technologie, 2017)
Power-line communications (PLC) in traction batteries is a promising data bus concept for battery management systems. This work presents a channel modeling approach, as well as an analysis of the PLC channel behavior and noise based on measurements. Furthermore, single-carrier and multi-carrier communication systems are designed, evaluated by simulations, and compared among them.